Systematic Literature Review (SLR): (Hakikat Evaluasi dalam Perspektif Filsafat Pendidikan Islam) - Hilman Afif, Tansri Riziq; Usiono, Usiono (PAI RAFAH, 2024)
Learning evaluation is important for educators in every teaching and learning process. Evaluation should be carried out continuously and serve as a guide to improve things that need to be improved. Learning evaluation must be well planned and related to the supporting factors of education in order to determine the effectiveness of the teaching and learning process that has been carried out to achieve the set goals. This research is a literature study that uses the Systematic Review (SR) method or more commonly known as Systematic Literature Review (SLR). This method is a systematic technique for collecting, critically evaluating, integrating, and compiling the results of various studies related to research questions or topics to be studied. The research process begins with searching for articles that are relevant to the research topic to be studied. The results of the analysis of all the journals studied concluded that evaluation is so important and must be owned by every individual or institution, including educational institutions. Evaluation is used to measure whether the educational objectives that have been formulated have been achieved or not. Although it does not reach the word 'perfect', evaluation can help us to continue to develop for the better in personal life, family, society, nation, and state.